'The Sermons in the Stones of Germany Preach Nihilism': 'Outsider Rubble Literature' and the Reconstruction of Germany, 1945–1949. (June 2016) - Feigel, Lara
Abstract : This article explores the literature and film produced by the writers and filmmakers sent by the British and Americans to occupied Germany in the four years after the war. Although these figures were intended to help transform the mentality of the Germans, it is argued here that they had less effect on Germany than Germany had on them, and that the crucial (albeit unwitting) result of their visits to Germany was the creation of a genre of art here named 'outsider rubble literature' or Fremdentrümmerliteratur. This is a genre that asked, ultimately, what right the Allies had to judge Germany from outside when they were guilty too. It comprises a series of fundamentally ambivalent works of art that often manifest their ambivalence by juxtaposing the two forms of destruction experienced in Germany: the destruction of the bombed cities and the destruction wrought in the concentration camps. The article suggests that this genre of 'outsider rubble literature' includes Thomas Mann's great postwar novel Doktor Faustus, arguing that our understanding of this novel is increased if we read it alongside the postwar writing of Stephen Spender, Martha Gellhorn and Klaus Mann, and the postwar filmmaking of Billy Wilder.